1981
DOI: 10.1042/bj1960391
|View full text |Cite
|
Sign up to set email alerts
|

Calcium uptake in isolated brush-border vesicles from rat small intestine

Abstract: Ca2+ uptake in brush-border vesicles isolated from rat duodena was studied by a rapid-filtration technique. Ca2+ uptake showed saturation kinetics, was dependent on the pH and ionic strength of the medium and was independent of metabolic energy. Uptake activity was readily inhibited by Ruthenium Red, La3+, tetracaine, EGTA, choline chloride and Na+ or K+. The effect of variations in medium osmolarity on Ca2+ uptake and the ionophore A23 187-induced efflux of the cation from preloaded vesicles indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
21
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 41 publications
10
21
0
Order By: Relevance
“…This is supported by the observations of others showing that (a) isolated brush border membrane vesicles from animals treated with D3 (or a D3 metabolite) accumulate calcium more rapidly than do those from vitamin D-deficient animals (9,(33)(34)(35), and (b) cortisol inhibits 1,25(OH)2D3-mediated calcium absorption by chick intestine (18,35) but has no effect on the 1,25(OH)2D3-dependent uptake of calcium by isolated brush border vesicles (35), indicating that the rate-determining transfer step was not at the brush border but elsewhere in the transport path.…”
Section: Resultssupporting
confidence: 76%
“…This is supported by the observations of others showing that (a) isolated brush border membrane vesicles from animals treated with D3 (or a D3 metabolite) accumulate calcium more rapidly than do those from vitamin D-deficient animals (9,(33)(34)(35), and (b) cortisol inhibits 1,25(OH)2D3-mediated calcium absorption by chick intestine (18,35) but has no effect on the 1,25(OH)2D3-dependent uptake of calcium by isolated brush border vesicles (35), indicating that the rate-determining transfer step was not at the brush border but elsewhere in the transport path.…”
Section: Resultssupporting
confidence: 76%
“…i.e., in the range reported by other investigators (12,(22)(23)(24)(25). Our space measurements were made at equilibrium in the medium we used for calcium uptake studies (100 mM KCl, 5 mM MgC12, and 20 mM Hepes-Tris, pH 7.…”
Section: Resultssupporting
confidence: 70%
“…They prepared duodenal vesicles from male rats fed a low calcium (0.06%) and low phosphorus (0.2%) semisynthetic diet for several days. Miller and Bronner (22) found that calcium uptake at 0.5 min showed saturation kinetics. Scatchard-plot analysis was used to define high (K. 2.7 X 104 M-l) and low (K. 60 M-1) affinity testine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process does not require ATP. Administration of 1,25(OH)2D in vivo to vitamin D-deficient chicks results in an enhanced ability of the subsequently isolated BBMV to accumulate calcium (5,10,11). Hypotheses explaining this effect include the synthesis of new proteins such as IMcal (12) or the vitamin D-dependent calciumbinding protein (13), and changes in the lipid composition of the BBM (14,15).…”
mentioning
confidence: 99%